Efficient Solid‐Phase Synthesis of pppRNA by Using Product‐Specific Labeling1. (25th March 2014) - Goldeck, M.; Tuschl, T.; Hartmann, G.; Ludwig, J.
Abstract A novel solid‐phase synthesis and purification strategy for 5′‐triphosphate oligonucleotides by using lipophilic tagging of the triphosphate moiety is reported. This is based on triphosphate synthesis with 5′‐O‐cyclotriphosphate intermediates, whereby a lipophilic tag, such as decylamine, is introduced during the ring‐opening reaction to give a linear gamma‐phosphate‐tagged species. This method enables the highly efficient synthesis of 5′‐triphosphorylated RNA derivatives and their gamma‐phosphate‐substituted analogues and will especially facilitate the advancement of therapeutic approaches that make use of 5′‐triphosphate oligonucleotides as potent activators of the cytosolic immune sensor RIG‐I.